Radiological Diagnosis and Differential Diagnosis of Headache - Langner, S.; Kirsch, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Headache is very common and affects almost everyone at some point. It is one of the most common disorders that leads patients to see their physician. All different forms have the nociception via trigeminal nerve fibers in common. Beside the clinical course headaches are classified as either primary or secondary, with the latter having an identifiable structural or biochemical cause. Imaging has a low diagnostic yield in primary headache but play an important role in the differential diagnosis of secondary forms. An overview of different forms of secondary headache is given, outlining diagnostic procedures and the morphologic imaging features of each syndrome.Key points:• Headache can be differentiated in primary and secondary forms.• Imaging plays an important role in differential diagnosis of secondary forms.• Imaging should be performed in patients with concomitant systemic or neurologic symptoms.Citation Format:• Langner S, Kirsch M, Hosten N Radiological Diagnosis and Differentialdiagnosis of Headache. Fortschr Röntgenstr 2015; 187: 879 – 891
Keywords: brain; head/neck; CT; MR-imaging